STRUCTURE PLOT: a program for drawing elegant STRUCTURE bar plots in user friendly interface - Ramasamy, Ramesh Krishnan; Ramasamy, Sumathy; Bindroo, Bharat Bushan; Naik, V Girish (SpringerPlus, 2014)
Background Understanding structure of the population is one of the major objective of many genetic studies. The program STRUCTURE is commonly used to infer population structure using multi-locus genotype data. However, a tool with graphical-user interface is currently not available to visualize STRUCTURE bar plots. Results We introduce STRUCTURE PLOT, a program for drawing STRUCTURE bar plots. The program generates publication ready, aesthetic STRUCTURE bar plots by using individual Q matrix from STRUCTURE or CLUMPP output. The program is very simple to use and includes variety of options like sorting bar by original order or by K, and selection of colors from R colors or RColorBrewer palette. Individual or population labels can be printed below or above the plot in any angle. Size of the graph and label can be defined, and option is provided to save plot in variety of picture formats in user defined resolution. Conclusion The program is implemented as a web application for online users and also as a standalone shiny application. Web application is compatible to majority of leading web browsers and standalone version can be launched using a simple R command. The program can be freely accessed at http://btismysore.in/strplot.